2002
DOI: 10.1124/jpet.300.3.746
|View full text |Cite
|
Sign up to set email alerts
|

Functional Involvement of Rat Organic Anion Transporter 3 (rOat3;Slc22a8) in the Renal Uptake of Organic Anions

Abstract: Our previous kinetic analyses have shown that the transporter responsible for the renal uptake of pravastatin, an HMG-CoA reductase inhibitor, differs from that involved in its hepatic uptake. Although organic anion transporting polypeptides are now known to be responsible for the hepatic uptake of pravastatin, the renal uptake mechanism has not been clarified yet. In the present study, the involvement of rat organic anion transporter 3 (rOat3; Slc22a8) in the renal uptake of pravastatin was investigated. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
133
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(148 citation statements)
references
References 26 publications
(37 reference statements)
13
133
2
Order By: Relevance
“…The mechanism by which urinary excretion of olmesartan was reduced after the co-administration of pravastatin is unclear and still needs to be clarified. Recent in vitro studies indicated that organic anion transporter 3 (OAT3) expressed at the basolateral membrane of renal proximal tubule epithelial cells is predominantly involved in renal uptake of both pravastatin and olmesartan (Hasegawa et al 2002;Yamada et al 2007). The drug-drug interaction via OAT3 between pravastatin and olmesartan may account for the reduction of olmesartan renal excretion in the co-administration phase; however, the interaction via MRP2, which also is expressed in the kidney, cannot be ruled out (Kivistö et al 2005;Nakagomi-Hagihara et al 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which urinary excretion of olmesartan was reduced after the co-administration of pravastatin is unclear and still needs to be clarified. Recent in vitro studies indicated that organic anion transporter 3 (OAT3) expressed at the basolateral membrane of renal proximal tubule epithelial cells is predominantly involved in renal uptake of both pravastatin and olmesartan (Hasegawa et al 2002;Yamada et al 2007). The drug-drug interaction via OAT3 between pravastatin and olmesartan may account for the reduction of olmesartan renal excretion in the co-administration phase; however, the interaction via MRP2, which also is expressed in the kidney, cannot be ruled out (Kivistö et al 2005;Nakagomi-Hagihara et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Pravastatin is an inhibitor of 3-hydroxy-3-methylglutaryl coenzyme A reductase used for the treatment of hypercholesterolemia. Although pravastatin is not significantly metabolized by cytochrome P450 (CYP) isoenzymes, cumulative evidence has suggested that multiple membrane transporters are involved in the absorption (Kobayashi et al 2003), hepatobiliary excretion (Hirano et al 2005;Kivistö et al 2005;Nakai et al 2001), and renal excretion (Hasegawa et al 2002) of pravastatin. Organic anion transporting polypeptide (OATP) 1B1 (gene SLCO1B1) is an uptake transporter expressed at the sinusoidal membrane of hepatocytes, mediating the uptake of various endogenous and exogenous substances from the blood circulation into hepatocytes in a sodium-independent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Western blotting was performed as described previously (8). ECL advance Western blotting Detection reagent (Amersham Pharmacia Biotech, Buckinghamshire, UK) was used for detection.…”
Section: Western Blottingmentioning
confidence: 99%
“…The classic basolateral OAT system, long referred to as the p-aminohippurate (PAH) transporter, was originally identified as novel kidney transporter (NKT) (24), which was proposed to function in renal organic ion secretion and was later directly shown to function in this capacity and named OAT1 (7,34). The other primary candidate for basolateral OA uptake is OAT3, originally identified as Roct [reduced in osteosclerosis (oc) transporter] (4), and several immunohistochemical studies have localized both OAT1 and OAT3 to the basolateral membrane of the proximal tubule of human, rat, and mouse (1,8,15,16,20,23,26,35). When expressed in Xenopus oocytes or epithelial cell lines, OAT1 couples OA entry to dicarboxylate exit and was trans-stimulated by preloading with PAH (34).…”
mentioning
confidence: 99%